Early changes in white matter pathways of the sensorimotor cortex in premanifest Huntington's disease. - Dumas, E; van den Bogaard, S; Ruber, M; Reilman, R; Stout, J; Craufurd, D; Hicks, S; Kennard, C; Tabrizi, S; Buchem, v; van der Grond, J; Roos, R (2012)
OBJECTIVES: To investigate the function-structure relationship of white matter within different stages of Huntington's disease (HD) using diffusion tensor imaging (DTI). EXPERIMENTAL DESIGN: From the TRACK-HD study, an early stage HD group and a premanifest gene carrier group (PMGC) were age-matched to two healthy control groups; all underwent 3-T MRI scanning of the brain. Region of interest (ROI) segmentation of the corpus callosum, caudate nucleus, thalamus, prefrontal cortex, and sensorimotor cortex was applied, and the apparent fiber pathways of these regions were analyzed. Functional measures of motor, oculomotor, cognition, and behavior were correlated to DTI measures. PRINCIPLE OBSERVATIONS: In PMGC versus controls, higher apparent diffusion coefficient (ADC) was seen in white matter pathways of the sensorimotor cortex (P < 0.01) and in the ROI of corpus callosum (P < 0.017). In early HD, fiber tract analysis showed higher ADC in pathways of the corpus callosum, thalamus, sensorimotor, and prefrontal region (P < 0.01). ROI analysis showed higher diffusivity in the corpus callosum and caudate nucleus (P < 0.017). Motor, oculomotor, cognition, and probability of onset within 2 and 5 years, correlated well with ADC measures of the corpus callosum (P < 0.01 - P < 0.005), sensorimotor (P < 0.01 - P < 0.005), and prefrontal region (P < 0.01). CONCLUSIONS: Disturbances in the white matter connections of the sensorimotor cortex can be demonstrated not only in manifest HD but also in premanifest gene carriers. Connectivity measures are well related to clinical functioning. DTI measures can be regarded as a potential biomarker for HD, due to their ability to objectify changes in brain structures and their role within brain networks.